1981
DOI: 10.1111/j.1464-410x.1981.tb03275.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostatodynia—Physiological Characteristics and Rational Management with Muscle Relaxants

Abstract: Patients with a clinical diagnosis of prostatodynia were evaluated by bacteriological, urodynamic and psychological means. In a prospective study 27 patients were entered on a trial of phenoxybenzamine, baclofen and placebo. A 50% symptomatic response was reported with phenoxybenzamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 6 publications
(4 reference statements)
1
32
0
6
Order By: Relevance
“…Some studies [5, 6] ]had addressed the urodynamic findings of these patients. Barbalias [7]studied a group of patients having prostatodynia and found that the Q max ranged from 4 to 33 ml/s, with a mean of 10.5 ml/s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [5, 6] ]had addressed the urodynamic findings of these patients. Barbalias [7]studied a group of patients having prostatodynia and found that the Q max ranged from 4 to 33 ml/s, with a mean of 10.5 ml/s.…”
Section: Discussionmentioning
confidence: 99%
“…Some urodynamic studies were undertaken in these patients [5, 6, 7, 8]. Discrepancies exist about the prevalence of urodynamic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Osborn et al [9] reported that a combination of phenoxybenzamine, baclofen and placebo is very effective in relieving the symptoms of chronic prostatitis (CP). This study Fig.…”
Section: A Brief Review Of Clinical Trialsmentioning
confidence: 99%
“…Patients with CPPS are thought to have an altered sensation of the perineum in comparison to control patients without CP/CPPS. The mechanism of this 'altered' innervations is poorly understood and is thought to be related to reflex sympathetic dystrophy of the perineum and pelvic floor [43][44][45].…”
Section: C Neurologicalmentioning
confidence: 99%